Innovations for Tomorrow: Summary of the 2016 Disaster Health Education Symposium. (17th January 2017) - Gulley, Kelly; Strauss-Riggs, Kandra; Kirsch, Thomas D.; Goolsby, Craig
Abstract: In an effort to enhance education, training, and learning in the disaster health community, the National Center for Disaster Medicine and Public Health (NCDMPH) gathered experts from around the nation in Bethesda, Maryland, on September 8, 2016, for the 2016 Disaster Health Education Symposium: Innovations for Tomorrow . This article summarizes key themes presented during the disaster health symposium including innovations in the following areas: training and education that saves lives, practice, teaching, sharing knowledge, and our communities. This summary article provides thematic content for those unable to attend. Please visit http://ncdmph.usuhs.edu/ for more information. ( Disaster Med Public Health Preparedness . 2017;11:160–162)